Morpholino-Mediated Knockdown of Ciliary Genes in Euplotes vannus, a Novel Marine Ciliated Model Organism - Tang, Danxu; Wang, Xiaoyu; Dong, Jingyi; Li, Yuan; Gao, Feng; Xie, Haibo; Zhao, Chengtian (Frontiers in Microbiology, 2020)
Cilia are highly conserved organelles present in almost all types of eukaryotic cells, and defects in cilia structure and/or function are related to many human genetic disorders. Single-celled ciliated protists, which possess diverse types of cilia, are remarkable model organisms for studying cilia structures and functions. Euplotes vannus is a representative ciliate with many intriguing features; for example, it possesses extensively fragmented somatic genomes and a high frequency of +1 programmed ribosomal frameshifting. However, the molecular mechanisms underlying these remarkable traits remain largely unknown, mainly due to the lack of efficient genetic manipulation tools. Here, we describe the first application of a morpholino-based strategy to knockdown gene expression in E. vannus. Through interfering with the function of two ciliary genes, ZMYND10 and C21ORF59, we showed that these two genes are essential for the ciliary motility and proliferation of E. vannus cells. Strikingly, both ZMYND10- and C21ORF59-knockdown cells developed shorter cilia in the ventral cirri, a special type of ciliary tuft, suggesting a novel role for these genes in the regulation of cilia length. Our data provide a new method to explore gene function in E. vannus, which may help us to understand the functions of evolutionarily conserved cilia-related genes as well as other biological processes in this intriguing model.